Hard carbon spheres prepared by a modified Stöber method as anode material for high-performance potassium-ion batteries. Issue 24 (21st April 2021) - Fan, Chenyang; Ou, Mingyang; Wei, Peng; Xu, Jia; Sun, Shixiong; Liu, Yi; Xu, Yue; Fang, Chun; Li, Qing; Han, Jiantao
Abstract : A modified Stöber method synthesizes resorcinol-formaldehyde resin-based secondary particle hard carbon spheres as anode material for high-performance potassium-ion batteries. Abstract : The Stöber method is a highly efficient synthesis strategy for homogeneous monodisperse polymer colloidal spheres and carbon spheres. This work delivers an extended Stöber method and investigates the synthesis process. By calcining the precursor under appropriate conditions, solid secondary particles of amorphous carbon (SSAC) and hollow secondary particles of graphitized carbon (HSGC) can be directly synthesized. The two materials have a nano-primary particle structure and a closely-packed sub-micron secondary particle structure, which can be used in energy storage. We find that SSAC and HSGC have high potassium-ion storage capacity with reversible capacities of 274 mA h g −1 and 283 mA h g −1 at 20 mA g −1 respectively. Significantly, SSAC has better rate performance with a specific capacity of 107 mA h g −1 at 1 A g −1 .